Synthesis of silver nanoparticles associated with denture adhesive: an antimicrobial approach against Candida albicans biofilms - Peralta, Laura Catali Ferreira (2022)
The association of antimicrobial compounds with prosthetic adhesives can be considered a promising alternative for users of complete dentures, because, in addition of helping to retain the denture during masticatory forces, it can collaborate in the treatment and/or prevention of prosthetic stomatitis, also in infections in the supporting mucosa caused mainly by the colonization of the fungus Candida albicans on the inner surface of the denture in the form of a biofilm, providing better oral health and quality of life conditions for the edentulous population. In this context, nanotechnology has gained ground in Dentistry, since nanoparticles, especially silver, have antimicrobial potential and prove to be biocompatible and can be used in the treatment of oral infections. Additionally, nanotechnology offers numerous advantages for laboratory studies of compounds with application in health and can become a great ally in the manufacture or improvement of dental materials. Thus, the aim of this study was to evaluate the antimicrobial activity of silver nanoparticles, synthesized by three distinct routes (Ultraviolet light method, Turkevich method and green chemistry method using Glycine max extract), associated with the COREGA® powder prosthetic adhesive against the biofilm of C. albicans. For this purpose, thermopolymerizable acrylic resin specimens were made as a substrate (n=3 per group). Afterwards, the surface of the specimens were treated with the association of the denture adhesive and silver nanoparticles, synthesized by the ultraviolet light method (AD + Ag UV group), the Turkevich method (AD + Ag Turk) and the green chemistry method using Glycine max extract (AD + Ag Gm). As controls, specimens were treated with nystatin associated with the patch (AD + Nist group), only the patch (AD group) or were submerged in PBS (PBS group). After the treatments, the biofilm of C. albicans were developed for 3, 6 and 12 hours on the surface of the specimens. Subsequently, analyzes were carried out for antimicrobial activity and fungal cell viability, through the minimum inhibitory and fungicidal concentration, by quantifying the colony-forming units per milliliter, by the colorimetric assay of salts of tetrazolium and confocal laser scanning microscopy. Three independent experiments were carried out and the results were presented as mean ± standard deviation, considering significant values when p<0.05. After 3, 6 and 12 hours of biofilm development, the groups treated with adhesive and nanoparticles association, regardless of the route, presented a reduced fungal load and a percentage of reduction of biofilm metabolic activity 50% compared to the control groups, and these results were similar and/or better than those obtained with the treatment control group AD + Nist. It was concluded that silver nanoparticles synthesized by UV light, Turkevich method and by the green synthesis through Glycine max extract have excellent antimicrobial activity against Candida albicans biofilms. The combination of silver nanoparticles with COREGA® adhesive is an innovative alternative that can have a potential preventive effect for denture stomatitis.